High Resolution Method using Patch Circular Array - Mohammed Amine Ihedrane; Seddik Bri; El Fadl Adiba (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Smart antennas have recently received increasing for improving the performance of wireless radio systems. In this research article, we have used a patch antenna using uniform circular arrays (UCA) with central element for direction of arrival (DOA). A central element was added to arrays in order to increase steering capability of the proposed array. This geometry is used to determine the elevation and azimuth based on two famous algorithms of high resolution method: Matrix Pencil method (MP) and MUltiple Signal Classification (MUSIC).The comparison results demonstrate clearly that the matrix pencil is more accurate and stable to estimation of direction of arrival compared to the MUSIC algorithm.